The Adjustment of Membrane Lipid Metabolism Pathways in Maize Roots Under Saline–Alkaline Stress - Xu, Xiaoxuan; Zhang, Jinjie; Yan, Bowei; Wei, Yulei; Ge, Shengnan; Li, Jiaxin; Han, Yu; Li, Zuotong; Zhao, Changjiang; Xu, Jingyu (Frontiers in Plant Science, 2021)
Plants are frequently confronted by diverse environmental stress, and the membrane lipids remodeling and signaling are essential for modulating the stress responses. Saline-alkaline stress is an major osmotic stress affecting the growth and development of crops. In this study, an integrated transcriptomic and lipidomic analysis was performed, and the metabolic changes of membrane lipid metabolism in maize roots under saline-alkaline stress were investigated. The results revealed that phospholipids were major membrane lipids in maize roots, and phosphatidylcholine (PC) accounts for approximately 40% of the total lipids. Under 100 mmol NaHCO3 treatment, the level of PC decreased significantly (11-16%), and the parallel transcriptomic analysis showed an increased expression of genes encoding PLAs and PLD/NPC, which suggested an activated PC turnover under saline-alkaline stress. The plastidic galactolipids synthesis was also activated, and an abnormal generation of C34:6 galactolipids in 18:3 plants maize implied a plausible contribution from the prokaryotic pathway, which could be partially supported by the up-regulated expression of 3 putative plastid-localized PAP/LPPs. A comprehensive gene-metabolite network was constructed and the regulation of membrane lipid metabolism under saline-alkaline stress in maize was discussed.